THE MYTH OF METAPHOR SYMBOLS IN SPEECH I HAVE A DREAM - Zakaria, Zakaria; Hasyim, Muh; Tundreng, Syarifuddin (University of Kuningan, 2022)
The speech I Have A Dream is Martin Luther King's political speech, delivered in front of the Lincoln Memorial on August 28, 1963. In the text of speech there are several metaphorical symbols (language style) in conveying his message and protest attitude against the American legal and political system which is considered unfair. To fully understand the meaning and message of the speech, the research question is